James Joyce and Samaritan hospitality : postcritical and postsecular reading in Dubliners and Ulysses - Russell, Richard Rankin (Edinburgh University Press, 2023)
The first book-length treatment of Joyce and hospitality.
Keywords: Joyce, James, -- 1882-1941 -- Criticism and interpretation.; Joyce, James, -- 1882-1941. -- Dubliners.; Joyce, James, -- 1882-1941. -- Ulysses.; Joyce, James, -- 1882-1941; Dubliners (Joyce, James); Ulysses (Joyce, James); Hospitality in literature.; Good Samaritan (Parable); Literary Studies.; Hospitalité dans la littérature.; Bon Samaritain (Parabole); LITERARY CRITICISM / European / English, Irish, Scottish, Welsh.; Hospitality in literature; Criticism, interpretation, etc.